TANTANGAN DIGITALISASI ANTI PENCUCIAN UANG DARI PENIPUAN SIBER DI SEKTOR JASA KEUANGAN - Rinjani, Andini Gita; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Digital disruption in the financial services sector facilitates the evolution of the modus operandi of money launderers and revises the risk mapping of money laundering using cyber networks. However, the enactment of the Financial Services Authority Regulation Number 8 of 2023 concerning Implementation of Anti-Money Laundering, Combating Financing of Terrorism, and Counter-proliferation Financing of Weapons of Mass Destruction Programs in the Financial Services Sector does not necessarily reduce the number of Suspicious Financial Transaction Reports which indicates the financial services sector is still vulnerable used as a money laundering tool from cyber fraud. Using the normative method and a qualitative approach, the author describes the challenged factors in enforcing digital anti-money laundering in terms of Legal System Theory by Lawrence M. Friedman. The results indicate that the complexity of the digital money laundering development, lack of competence and quality of law enforcers, lack of strict sanction imposed, low utilization of sophisticated technology in line with the high costs charged, and lack of awareness and culture of law-abiding by public are challenges which shall immediately be addressed by the government, regulators, law enforcers, public, and financial service providers to optimize enforcement of digital anti-money laundering in the financial services sector.